Peran Guru dalam Meningkatkan Minat Belajar Siswa pada Masa Pandemi Covid-19 - Gloria Lie; Reni Triposa (Angelion, 2021)
Corona virus or Covid 19, first appeared in Wuhan, China. And Indonesia is one of the countries affected by the Corona virus. The emergence of Covid-19 and its rapid spread, made Indonesian educational institutions take action, to carry out the learning process from home. This refers to all levels of education from early childhood education to tertiary education. This makes students and educators inevitably have to change the learning method from face-to-face to online. From the educator or teacher side, they must rack their brains to maximize their role to continue teaching professionally. Teachers must further enhance their role in increasing students' learning interest during this increasingly prolonged online learning period. The Christian Religious Education teacher specifically has to practice and model its roles as taught by the Great Teacher of the Lord Jesus. Using the literature study approach in descriptive qualitative methods can describe the purpose of the research paper, namely to determine the role of Christian Religious Education teachers in increasing student interest in learning during the Covid-19 pandemic. The method used is literature study research with descriptive analysis method and descriptive qualitative approach. From this research it can be concluded that the role of teachers as educators, teachers, learners, trainers, facilitators, motivators, leaders, communicators, socialization agents, mentors, gospel preachers and also as conveyors of the truth should be increased as much as possible to increase student interest in learning during the pandemic and online teaching and learning process.Corona virus atau Covid 19, pertama kali muncul di Wuhan, China. Dan Indonesia merupakan salah satu negara yang terdampak virus Corona. Kemunculan Covid-19 dan penyebarannya yang begitu cepat, membuat lembaga pendidikan Indonesia mengambil tindakan, untuk melakukan proses pembelajaran dari rumah. Hal ini merujuk untuk semua tingkatan pendidikan mulai dari pendidikan usai dini hingga perguruan tinggi. Hal ini membuat siswa dan tenaga pendidik mau tidak mau harus mengubah metode pembelajaran yang semula tatap muka menjadi daring. Dari pihak pendidik atau guru, mereka harus memutar otak untuk memaksimalkan peran mereka untuk tetap mengajar dengan profesional. Guru harus lebih meningkatkan perannya dalam meningkatkan minat belaja siswa selama masa pembelajaran daring yang makin berkepanjangan ini. Guru Pendidikan Agama Kristen secara spesifik harus mempraktekkan dan mencontohkan peran-perannya seperti yang diajarkan oleh Guru Agung Tuhan Yesus. Dengan menggunakan pendekatan studi Pustaka dalam metode kualitatif deskritif dapat mendeskripsikan tujuan penelitian paper, yaitu  untuk mengetahui peran guru Pendidikan Agama Kristen dalam meningkatan minat belajar siswa pada masa pandemi Covid-19. Metode yang digunakan adalah penelitian studi pustaka dengan metode diskriptif analisi dan pendekatan kualitatif deskriptif. Dari penelitian ini dapat disimpulkan bahwa peran guru sebagai pendidik, pengajar, pembelajar, pelatih, fasilitator, motivator, pemimpin, komunikator, agen sosialisasi, pembimbing, pembeita injil dan juga sebagai penyampai kebenaran harus ditingkatkan semaksimal mungkin untuk meningkatkan minat belajar siswa selama masa pandemi dan proses belajar mengajar daring.